Meta-Analysis of Income and Price Elasticities Energy Demand: Some Public Policy Implications for Latin America - Galindo, Luis Miguel (2015)
The aim of this paper is to analyze the variation in empirical estimates of the income and price elasticities of energy demand. The evidence presented, through a meta-analysis, allows identification of the weighted average of the income and price elasticities, shows that the estimates are very heterogeneous, that there is publication bias, and that factors such as region, energy sector, among others, affect its volatility. The evidence also indicates that income elasticity in Latin America is greater than in the OECD countries, and that the price elasticity of energy demand is lower in Latin America than in the OECD countries. Therefore, continued economic growth in Latin America will be accompanied by a growth in energy demand. Moreover, the establishment of a tax in Latin America, under the current elasticities, is less effective and will be insufficient to control the increase in energy consumption.